ROLE OF MARINE A DEPARTMENT OF REVENUE IMPROVEMENT DISTRI EAST KUTAI - Bedris, Tandi (PREDIKSI, 2016)
Birth of law No.32 of 2004 on local go for local governments throughoutflexibilitythecout local governments, is a breakthrough that reform.Among the manythoritydecent(provalidzed) aub government to regency.It’soauthoritygovernmentisoften in which authorityisthe that can potentially gene including the government's authority to m oil and gas, marine fisheries and othe geographical conditions of each area.East Kutai Regency as an largeutonomousseaandre coastline stretches.Geographical conditio provide opportunities for the East Kuta secFisheries.torexpectedpotentialto isbe used by the lo Kutai.This will be a significant opportu (PAD) to support the promotion of East Ku Therefore, the potential oftothaveEast authority to manage natural resources is thorough so that thisNaturalpotentialresourcewealthcanfrombe theex fisheries sector has to be excellent.It revenues from the fisheries sector is incr increase has not bias rated as a success this sector.It is caused by, the achieve Marine eriesandFishAgency of East Kutai Regenc sector is notargetbiasedor re.achsultstheint after allThis condition is illustrated by the Financial ManagementEastKutaireadistrictofhetargetthatandde actual revenue receipts in particular ar and 2014 never reached the planned target homework by the Marine and Fisheries Age shouldreceive seriousfordevtheattentionlopmentofthefisheries sector.